Introducing a New Key Player in Internal Whistleblowing Procedures: Examining the Position of Confidential Advisers. (2nd January 2021) - Hoekstra, Alain; Talsma, Jitse
Abstract : Employee reports about suspected integrity violations and other types of wrongdoing are widely acknowledged as an important method for disclosing misconduct and improving the integrity of organizations. Organizations and employees may benefit from appointing Confidential Advisers (CAs) as part of their internal reporting procedures. Confidential Advisers inform employees about internal reporting, support employees in the reporting process, and can advise the organization on the improvement of its integrity management system. As such CAs can lower the threshold for internal reporting, improve the quality of the reports made, increase the chance that a report leads to an internal investigation, and consequently play an important role in resolving raised issues. This article explores how the CA position is currently organized in Dutch organizations and identifies conditions that could be relevant for future improvements based on a mixed–method research design.